Isotachophoretic determination of triethanolamine in cosmetic products - Janečková, Michaela; Bartoš, Martin; Lenčová, Jana (Springer, 2019)
In this article, determination of triethanolamine in cosmetic products by capillary isotachophoresis is presented. Because of EU which regulates maximal content of triethanolamine in cosmetics, it is important to control quality of cosmetic products. In contrast with chromatographic methods, the developed method is of low cost and samples can be analyzed without any pretreatment. Optimal conditions represented by electrolyte system for separation of triethanolamine as cation, 10mmol/dm(3) sodium acetate, 0.05% (m/m) hydroxyethyl cellulose (HEC), with acetic acid (leading electrolyte of pH 4.6) and 10mmol/dm(3) acetic acid (terminating electrolyte) were chosen. In this electrolyte system, the following analytical parameters were achieved: limit of detection 0.6 mu mol/dm(3), limit of determination 1.8 mu mol/dm(3), repeatability 3.5%, recovery 96.03.6%, linearity range 10-400 mu mol/dm(3). The developed method shows potential applicability on analysis of triethanolamine in any cosmetic products. [GRAPHICS] .
Izotachoforetické stanovení triethanolaminu v kosmetických produktech
Keywords: amino alcohols; electrophoresis; surfactants; aminoalkoholy; elektroforéza; povrchově aktivní látky